A rare case of chronic genian fistula with oral mucosal hair follicle inclusion: case report and review of the literature - Ciora, Edmond D.; Miron, Mariana I.; Igna, Andreea; Miron, Andreea G.; Roi, Ciprian I.; Riviș, Mircea (Frontiers in Oral Health, 2025)
BackgroundThis report describes a rare case of chronic genian fistula associated with inclusion of oral mucosal hair follicle. Ectopic hair growth in the oral cavity is extremely rare and is typically associated with grafting techniques. The presence of a chronic extraoral fistula with intraoral hair follicle inclusion is exceedingly uncommon and poses diagnostic and therapeutic challenges.Case presentationA 73-year-old male presented to the Oral and Maxillofacial Surgery Department in Timișoara (Romania) with a chronic cutaneous fistula in the right lower cheek region, unresponsive to antibiotics and without signs of dental or sinus origin. Clinical examination revealed a 0.5 cm cutaneous opening and a filamentous, hair-like structure emerging intraorally from the right maxillary alveolar crest. A submucosal fibrotic tract was palpable, and although the fistula was not clearly visible on CBCT due to its soft tissue nature, imaging confirmed the absence of bony or odontogenic involvement. Given the clear clinical presentation, surgical excision was performed under local anesthesia. Intraoperatively, a keratinized, hair-bearing tract traversing the cheek to the alveolar process was excised en bloc. Healing was uneventful, and no recurrence was observed at 14 days.ConclusionThis is one of the few reported cases of a genian fistula with intraoral hair follicle inclusion in a patient without prior facial surgery. The case highlights the importance of integrating clinical, radiologic, and histopathologic findings in diagnosing and managing rare fistulous tracts.